Osteotómie po zlomeninách distálneho rádia – päťročné klinické a rentgenologické výsledky - Cibula, Z; Hrubina, M; Melišík, M; Mudrák, I; Nečas, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY The purpose of our retrospective study is to evaluate 5-year functional and radiological outcomes in patients following corrective osteotomy of the distal radius and ulnar osteotomy for malposition after a distal radius fracture, to identify differences in the outcomes of corrective osteotomies depending on the type of the original fracture according to the AO classification, the grade of arthritis of radiocarpal (RC) joint, surgical approach and the way of stabilisation of the osteotomy. MATERIAL AND METHODS The followed-up group of 22 patients (8 men and 14 women) underwent osteotomy for malposition of distal radius in the period 2007-2011. The age of patients in the followed-up group ranged from 21 to 72 years, with the mean age of 51 years at the time of surgery. The indications for corrective osteotomy due to distal radius deformity were the following: functional limitation, pain and radiological parameters confirming the deformity. The opening wedge osteotomy of distal radius performed through volar or dorsal approach, isolated shortening osteotomy of ulna and a combination of both the methods were used. The observations included: the original type of fracture according to AO/OTA classification, functional outcomes - Disabilities of the Arm Shoulder and Hand (DASH) score, Mayo Wrist Score (MWS), range of motion, grade of wrist arthritis and specific complications. The follow-up period was 5 years. RESULTS Average results were obtained in the group of patients before/after the osteotomy: DASH score- 35/14, MWS- 54/77, flexion- 44°/64°, dorsiflexion- 48°/61°, supination- 75°/79°, pronation- 72°/83°, ulnar duction- 20°/23°, radial duction- 9°/16°, grip strength in percentage- 59%/83%. After osteotomy, a statistically significant increase was observed in flexion, dorsiflexion, supination, pronation, radial duction, ulnar duction, grip strength in percentage, MWS, while in the DASH score a statistically significant decrease was reported. Based on the statistical evaluation of differences in functional outcomes after osteotomy, in patients with type A and C original distal radius fractures no difference in range of motion parameters was found after osteotomy. As to the mean values, the flexion and dorsiflexion range of motion was greater by 10° in patients after extra-articular osteotomy for malposition following the type A original fracture as compared to the type C fracture. By measuring the Joint Space High (JSH) ratio, no statistically significant changes were found regarding the progression of arthrosis of the radiolunate and radioscaphoid part of the RC joint as against the arthrosis in patients up to 5 years after corrective osteotomy of the distal radius. In patients with distal radius malposition and RC joint grade 1-2 arthritis according to the Knirk and Jupiter classification, better functional outcomes were achieved than in the limited and total wrist arthrodesis. In our patients, at 5 years after osteotomy no worsening was observed of the existing wrist arthritis and no arthritis was newly diagnosed. Specific complications were found in 4 cases (18.2 %). In 2 patients after radial osteotomy from dorsal approach (extensor tendon irritation, rupture of the long extensor tendon of the thumb), removal of osteosynthesis material was necessary in both the patients. In one patient after the isolated ulnar shortening osteotomy, an intraoperative fissure of distal ulnar fragment was detected, which healed without any further complications. In one patient an iatrogenic fracture of anterior superior iliac spine was observed after harvesting the corticospongious graft from the ala of the ilium. DISCUSSION Corrective osteotomy is a well-established method for treating distal radius deformities following a fracture. Even at present, there are various opinions regarding the indications, contraindications, timing of the surgery, osteotomy technique and the need to use a bone graft. Limited or total wrist arthrodeses in the area of wrist arthrosis and deformities bring good results with respect to the pain relief, but a limited range of motion occurs mainly in younger patients. Bearing this in mind, in grade 1-2 wrist arthritis in patients with distal radius deformities, a better functional outcome can be achieved by osteotomy. By using dorsal or volar approach, comparable outcomes can be obtained, but with the dorsal approach there is higher frequency of complications and the need to remove the osteosynthesis material. CONCLUSIONS Corrective osteotomies resulted in an improved functional outcome in the treatment of deformities after a distal radius fracture. Apart from deformity correction, the treatment has been affected also by the RC joint arthritis. The study confirmed neither statistically significant differences in the osteotomy outcomes in patients with the original type A or type C distal radius fracture according to the AO classification, nor the statistical significance of the RC joint arthritis. Our results have proven better functional outcomes of deformity correction achieved by osteotomy in case of grade 1 and 2 arthritis than by the limited wrist arthrodesis. In patients showing arthritic changes, no progression was reported within five years after the osteotomy. Key words: distal radius fracture, distal radius deformity, osteotomy, functional results.
Keywords: Wrist Joint; Radius; Fractures, Malunited; Humans; Radiography; lidé středního věku; osteotomie; radiografie; Wrist Injuries; následné studie; Female; poranění zápěstí; radius; Range of Motion, Articular; fraktury vřetenní kosti; lidé; zápěstní kloub; obnova funkce; Postoperative Complications; Radius Fractures; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Recovery of Function; Czech Republic; špatně zhojené fraktury; rozsah kloubních pohybů; Česká republika; mužské pohlaví; Osteotomy; Follow-Up Studies